TRADITION AND INNOVATION IN ARCHITECTURE KHARKIV THEATRE - , О. М. (Municipal economy of cities. Series: «Economy science», 2013)
The article revealed features of creation and development of theater in Odessa, analyzed their architectural and planning decisions and typological features, as well as factors that have influence on the innovative theater architecture.